Synthesis and Characterisation of β-Cyclodextrin-Conjugated Carboxymethyl Chitosan Derivative for Antimicrobial and Wound Healing Applications - Renukadevi, S.; Kumar, B. Deepan; Priya, G. Hari Hara; Tamizharuvi, T.; Jaisankar, V. (Asian Journal of Chemistry, 2026)
Chitosan can be chemically modified to form a range of derivatives to perform enhanced biological activities with enhanced solubility in water and functional properties. These alterations have tunned their applications towards biomedical fields. This work aims to synthesize the carboxymethyl derivative of chitosan selectively functionalised at the C6 carbon atom through careful masking of the C2 location. In this regard, the C2-amino group was shielded to avoid interfering with the carboxymethylation process at the C6 hydroxyl group. The functional characteristics of the chitosan derivative were further improved by conjugating it with β-cyclodextrin to form a β-cyclodextrin-carboxymethyl chitosan (CD-CMCh) derivative. Further biological potential was tested on the derivative emphasizing its significant activity against the bacteria S. aureus (13 ± 2 mm), E. coli (9 ± 1 mm) and K. pnemoniae (11 ± 2 mm) at the concentration of 1000 µg/mL, along with the potent activity against fungal A. niger (19 ± 5.7 mm, 16.37 ± 7.6 mm) and T. viride (13.3 ± 3.5 mm, 12.7 ± 5 mm) at the concentration 1000 and 500 µg/mL, respectively than C. albicans. Furthermore, the in vitro wound healing assay revealed a 65% wound closure, indicating substantial cell migration and regenerative potential. Results revealed that this selectively modified derivative is a flexible molecule in the production of biomedical materials and thus holds great promise for application in antimicrobial treatments and wound healing therapy.